The 14th election to India's Lower House - Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2004)
The election to India's lower house of parliament (Lok Sabha), which took place in five phases between April 20 and May 20, 2004, resulted in three major surprises. First, contrary to all forecasts, the opposition Congress Party and its United Progressive Alliance (UPA) defeated the ruling Bharatiya Janata Party (BJP) and the National Democratic Alliance (NDA). Second, Manmohan Singh became India's first Sikh prime minister. And third, against all expectations, the country's communist parties polled their best results ever.The election's outcome underlined the trend towards regionalization of India's party system and strengthened the country's secular forces. But voters once again failed to produce clear majorities. The new Congress Party-led minority government will have to depend on cooperation with the communist parties. Thanks to the basic consensus among the large parties concerning key foreign and economic issues, the liberalization and reform of India's economy will continue. However, future economic policy will pay greater attention to rural areas. (SWP Comments / SWP)
Keywords: 320